2022
DOI: 10.3390/foods11020202
|View full text |Cite
|
Sign up to set email alerts
|

Whole Wheat Crackers Fortified with Mixed Shrimp Oil and Tea Seed Oil Microcapsules Prepared from Mung Bean Protein Isolate and Sodium Alginate

Abstract: Shrimp oil (SO) rich in n-3 fatty acids and astaxanthin, mixed with antioxidant-rich tea seed oil (TSO), was microencapsulated using mung bean protein isolate and sodium alginate and fortified into whole wheat crackers. SO and TSO mixed in equal proportions were emulsified in a solution containing mung bean protein isolate (MBPI) and sodium alginate (SA) at varied ratios. The emulsions were spray-dried to entrap SO-TSO in MBPI-SA microcapsules. MBPI-SA microcapsules loaded with SO-TSO showed low to moderately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The wall material depends on its emulsifying property as a protective barrier, which can form stable oil‐in‐water emulsions to encapsulate core materials. MBPs have attracted immense attention as carriers for encapsulation because of their unique techno‐functional and nutritional properties (Gulzar et al., 2022). MBPs have been used to load curcumin by forming hydrophobic interactions and hydrogen bonds.…”
Section: Food Applications Of Mbpsmentioning
confidence: 99%
“…The wall material depends on its emulsifying property as a protective barrier, which can form stable oil‐in‐water emulsions to encapsulate core materials. MBPs have attracted immense attention as carriers for encapsulation because of their unique techno‐functional and nutritional properties (Gulzar et al., 2022). MBPs have been used to load curcumin by forming hydrophobic interactions and hydrogen bonds.…”
Section: Food Applications Of Mbpsmentioning
confidence: 99%
“…68 Emulsifying properties MBP is an amphiphilic protein as a macromolecule composed of both hydrophobic and hydrophilic amino acids and thus it can be used as an emulsifier. 75 The emulsifying activity (EA) of MBPI in distilled water (63.18%) was significantly higher than that of 3% NaCl solution (72.03%). 11 Similarly, a higher emulsion stability (ES) of MBPI was observed in 3% NaCl because the salt solution can stabilize the system by reducing the force of adjacent droplets.…”
Section: Water and Oil Absorption Capacitymentioning
confidence: 93%
“…MBP is an amphiphilic protein as a macromolecule composed of both hydrophobic and hydrophilic amino acids and thus it can be used as an emulsifier 75 . The emulsifying activity (EA) of MBPI in distilled water (63.18%) was significantly higher than that of 3% NaCl solution (72.03%) 11 .…”
Section: Functional Properties Of Mbpmentioning
confidence: 99%
“…Recently, Loncarevic et al 88 added encapsulated green tea extract to white chocolate to improve its polyphenol content and antioxidant capacity. Besides, Gulzar et al 89 prepared the spray-dried microcapsules using sodium alginate and mung bean protein isolate to coencapsulate tea seed oil as an antioxidant and shrimp oil rich in n − 3 fatty acids and astaxanthin, which were fortified into whole wheat crackers. The authors found that these whole wheat crackers not only had excellent oxidative stability and retention of polyunsaturated fatty acids during storage but also had good organoleptic properties.…”
Section: Application Of the Tea-based Delivery Systemmentioning
confidence: 99%